2023
DOI: 10.1021/acssensors.2c02089
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional van der Waals Heterostructure-Based Nanocages as Supersensitive 3-Hydroxy-2-butanone Gas Sensors at Room Temperature

Abstract: 3-Hydroxy-2-butanone is one of the biomarkers of Listeria monocytogenes, which is quite important for the intelligent detection of 3H-2B. However, it is still a challenge to fabricate sensing materials obtaining excellent sensitivity and selectivity under the ppb-level detection limit. Herein, a plasma-assisted synthetic approach was proposed for the construction of hierarchical nanostructures and the simultaneous loading of TAPP-COFs, which could reduce interlayer interaction and convert the metallized sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…37 Other different types of defects have already been characterized by EPR spectroscopy, providing a new insight into gas sensing materials and the corresponding underlying sensing mechanisms (Table 3). [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Table 3 Summary of typical gas sensing materials and the corresponding EPR results…”
Section: Applications Of Epr In Gas Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Other different types of defects have already been characterized by EPR spectroscopy, providing a new insight into gas sensing materials and the corresponding underlying sensing mechanisms (Table 3). [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Table 3 Summary of typical gas sensing materials and the corresponding EPR results…”
Section: Applications Of Epr In Gas Sensorsmentioning
confidence: 99%
“…37 Other different types of defects have already been characterized by EPR spectroscopy, providing a new insight into gas sensing materials and the corresponding underlying sensing mechanisms (Table 3). 38–54…”
Section: Epr In Gas Sensorsmentioning
confidence: 99%
“…Herein, we study the effect of plasma treatment of tin dioxide films on their surface and photocatalytic properties, which are selected for analysis due to their close relationship with the adsorption and sensor functionalities. While such processing is frequently employed as a manufacturing operation to produce semiconductor devices [15][16][17][18], it has also been found that oxygen plasma treatment improves the performance of metal oxide gas sensors [13,19,20]. The analysis of literature sources also shows that plasma treatment leads to a significant improvement in the photocatalytic properties of semiconductor oxides.…”
Section: Introductionmentioning
confidence: 99%